Evaluación de la satisfacción de la calidad del servicio recibido según el modelo SERVPERF de los clientes de la distribuidora Almapo SRL. del distrito de Trujillo, febrero 2013 - Ruiz Ydrogo, Rolland Nilton (2013)
This thesis report entitled "EVALUATION OF SATISFACTION OF SERVICE QUALITY MODEL SERVPERF RECEIVED BY CUSTOMERS OF THE DISTRIBUTOR ALMAPO SRL. DISTRICT OF TRUJILLO. FEBRUARY 2013 "is a descriptive and cross in order to assess the satisfaction of quality of service received by the customer Servperf model of distributor Almapo SRL. Trujillo District. February 2013, in fact meet the needs and expectations of customers and increase the competitiveness of the distributor Almapo SRL.A survey was applied to collect information and use a service quality model "Model Servperf" to measure the satisfaction of the quality of service received from customers of the distributor Almapo SRL, which consists of five dimensions (tangibility , Reliability, responsiveness, Warranty, Empathy) SERVPERF survey with Likert scale, a random sample stratified by winery size, 82 Almapo distributor customers. It was found that the level of customer satisfaction of customers is average. In conclusion this will help the company to identify its strengths and weaknesses according to the user's perception about the quality of service provided and / or adapt models possible responses to customer dissatisfaction that offers the service product and switch any negative idea that a customer about the service received by the distributor Almapo SRL